2018
DOI: 10.3390/app8040546
|View full text |Cite
|
Sign up to set email alerts
|

Three Flow Features behind the Flow Control Authority of DBD Plasma Actuator: Result of High-Fidelity Simulations and the Related Experiments

Abstract: Both computational and experimental studies are conducted for understanding of the flow separation control mechanism of a DBD (dielectric barrier discharge) plasma actuator. Low speed flows over an airfoil are considered. A DBD plasma actuator is attached near the leading edge of an airfoil and the mechanism of flow control of this small device is discussed. The DBD plasma actuator, especially in burst mode, is shown to be very effective for controlling flow separation at Reynolds number of 6.3 × 10 4 , when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Using the string-type Pa, the suppression of turbine tip clearance flow and feedback control of flow separation on an NACA0015 airfoil have been presented by experiments [28,29]. These cases have verified the performance of the string-type Pa in flow control around a two-dimensional curved surface that has been reported by many researchers [8][9][10][11][12].…”
Section: Tested Model and Flow Conditionsupporting
confidence: 61%
See 1 more Smart Citation
“…Using the string-type Pa, the suppression of turbine tip clearance flow and feedback control of flow separation on an NACA0015 airfoil have been presented by experiments [28,29]. These cases have verified the performance of the string-type Pa in flow control around a two-dimensional curved surface that has been reported by many researchers [8][9][10][11][12].…”
Section: Tested Model and Flow Conditionsupporting
confidence: 61%
“…From a safety perspective, high voltage AC was applied to the Cu wire, and the exposed electrode was connected to the ground (GND). To date, experimental [3,4,[8][9][10] and numerical [11,12] studies have been conducted and shown the possibilities of improvement in the lift-to-drag ratio and increasing the stall angle using the sheet-type Pa installed near the leading edge of the airfoil as well as the effectiveness of modulation drive. Moreover, control methods of flow fields on more complex shaped 3D bluff bodies have been investigated.…”
Section: Tested Model and Flow Conditionmentioning
confidence: 99%
“…With regard to transportation equipment, PA has also been applied to flow around wings, railway pantographs (Mitsumoji et al, 2012), automobile bodies, and others. In particular, many studies focusing on improvement of wing performance by suppressing the flow separation (Sato et al, 2015;Fujii, 2018) have been conducted in the aerospace field. Regarding applications of PA on automobile flow, aerodynamic noise reduction (Miyamoto et al, 2018) and aerodynamic drag reduction (Shadmani et al, 2018;Kanatani et al, 2009;Vernet et al, 2018) have been studied.…”
Section: Aerodynamic Drag Reduction Of a Simplified Vehicle Model By mentioning
confidence: 99%
“…In reference [12], a DBD plasma actuator, attached near the leading edge of an airfoil and operating in burst mode, is shown to be very effective for controlling flow separation at a Reynolds number of 6.3 × 10 4 , when applied to the flows at an angle of attack higher than the stall. In the paper, guidelines for the effective use of DBD plasma actuators are proposed.…”
Section: Flow Control Applicationsmentioning
confidence: 99%